Design and 3D bioprinting of interconnected porous scaffolds for bone regeneration. An additive manufacturing approach - Roque, Renan [UNESP]; Barbosa, Gustavo Franco; Guastaldi, Antonio Carlos [UNESP] (Elsevier B.V., 2021)
Scaffolds are very important element for bone regeneration issues. On this way, the purpose of this paper is the design and manufacturing of porous scaffolds fabricated by 3D printing technology from biodegradable thermoplastic polymers and calcium phosphates (in micrometric scale). So, the main aim of this research is to obtain complex porous 3D structures that present adequate mechanical properties in relation to bones, through a structured interconnectivity between the pores. Based on the 3D models of the designed scaffolds, selection and preparation of the biomaterials, the process parameters were set in order to provide conditions for the scaffolds? manufacturing. Using an additive manufacturing technology of pneumatic gelling liquid extrusion, with a bioprinter that uses pneumatic distribution system for continuous extrusion of material, two models of designed scaffolds were 3D printed and characterized by mechanical compression analyses and then, evaluated by Scanning Electron Microscopy (SEM) method. Results of Linear Static Analysis (LSA) showed that the 3D designed scaffolds meet the specifications required in the literature for specific rigidity (20?141 MPa). The stress x strain curves showed that the compressive strength values of the composite biomaterial used for all tested coupons are within the values described in the literature for trabecular bone application (range from 2 to 12 MPa). In addition, the pore sizes proven by micrographs have been within the range of application for tissue engineering (20?850 ?m), as mentioned by the literature too. Also, the SEM showed the repeatability related to the interconnectivity between pores, based on homogeneous and uniform structures, regarding adhesion between layers, dimensions of pores and constant extruded filament. Thus, development and applications of the biomaterial composed by Polycaprolactone and Amorphous Calcium Phosphate (PCL + ACP) faced to the additive manufacturing method used to perform the printing of designed scaffolds, can be considered a potential and promising novelty for application in tissue engineering field.
Keywords: 3D bioprinting; Scaffolds; Pneumatic gelling liquid extrusion; Bone regeneration